Songs on endless repeat essays and outtakes - So, Anthony Veasna 1992-2020 (Ecco, an imprint of HarperCollins Publishers, 2023)
The late Anthony Veasna So's debut story collection, Afterparties, was a landmark publication, and he was equally known for his comic, soulful essays. This volume gathers those essays together, along with previously unpublished fiction. Written with wit and an unflinching eye, the essays examine his youth in California, the lives of his refugee parents, his intimate friendships, loss, pop culture, and more. And in linked fiction following three Cambodian American cousins who stand to inherit their late aunt's illegitimate loan-sharking business, So explores community, grief, and longing with humor and depth
Keywords: So, Anthony Veasna / 1992-2020; Authors, American / 21st century / Biography; Gay authors / United States / Biography; Cambodian Americans / Biography; Refugees / Cambodia; Cambodian Americans / Fiction; Inheritance and succession / Fiction; Usury / Fiction; Écrivains américains / 21e siècle / Biographies; Écrivains homosexuels / États-Unis / Biographies; Américains d'origine cambodgienne / Biographies; Réfugiés / Cambodge; Américains d'origine cambodgienne / Romans, nouvelles, etc; Successions et héritages / Romans, nouvelles, etc; Usure / Romans, nouvelles, etc; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; American authors / Biography; Gay authors / Biography; Essays